PHYSICAL QUALITY OF BALI BEEF MARINATED WITH PALM NIRA WATER (Arenga pinnata) - N., Situmorang; Sriyani, N. L. P.; Oka, A. A. (Jurnal Peternakan Tropika, 2024)
The physical quality of meat is a very important thing to consider in processing meat because the good physical quality of meat will produce good products that are suitable for consumption. The research entitled Physical Quality of Bali Beef Marinated with Palm Nira Water (Arenga pinnata) aims to determine the effect of marinating Bali beef with palm juice water on the physical quality of the meat based on pH tests, water holding capacity, cooking losses, and meat color. This study used a completely randomized design (CRD) with 4 treatments and 4 replications. The treatment is P0 using fresh balinese beef without marination, P1 Bali beef marinated with 15% palm juice water, P2 Bali beef marinated with 20% palm juice, and P3 Bali beef marinated with 25% palm juice water. Each treatment was marinated for 40 minutes. The results obtained at pH are P0 (5,56), P1 (5,12), P2 (5,10), and P3 (5,04). Color is obtained consecutively P0 (4,75), P1 ( 3,75), P2 (3.25), and P3 (2.00). The water holding capacity is P0 (30,69), P1 (26,85, P2 (25.30), and P3 (22.50). The cooking losses obtained were P0 (32,77), P1 (34,44), P2 (35.15), and P3 (35.44). pH, meat color, and water holding capacity decreased significantly but cooking losses did not have a significant effect. Overall, the marination of bali beef with palm juice did not improve the physical quality of bali beef.